2018
DOI: 10.1016/j.cgh.2018.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Under-dilated TIPS Associate With Efficacy and Reduced Encephalopathy in a Prospective, Non-randomized Study of Patients With Cirrhosis

Abstract: In prospective, non-randomized study of patients with cirrhosis, we found under-dilation of PTFE-SGs during TIPS placement to be feasible, associated with lower rates of PSE, and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 21 publications
6
84
2
4
Order By: Relevance
“…34,35 Growing evidence has been published that suggests less complications after TIPS by using smaller diameter stents or dilatation of stents smaller than the nominal diameter, suggesting a beneficial effect of less shunt volume. [36][37][38][39][40] Regarding other decompensating events, we were unable to find a significant difference in variceal bleeding, hepatorenal syndrome or spontaneous bacterial peritonitis between patients with L-TSA and S-TSA. Considering variceal bleeding, our data are supported by previous reports, in which only the presence of SPSS vs. no SPSS was shown to be associated with bleeding, but no differences between small and large SPSS were detected.…”
Section: Discussioncontrasting
confidence: 60%
“…34,35 Growing evidence has been published that suggests less complications after TIPS by using smaller diameter stents or dilatation of stents smaller than the nominal diameter, suggesting a beneficial effect of less shunt volume. [36][37][38][39][40] Regarding other decompensating events, we were unable to find a significant difference in variceal bleeding, hepatorenal syndrome or spontaneous bacterial peritonitis between patients with L-TSA and S-TSA. Considering variceal bleeding, our data are supported by previous reports, in which only the presence of SPSS vs. no SPSS was shown to be associated with bleeding, but no differences between small and large SPSS were detected.…”
Section: Discussioncontrasting
confidence: 60%
“…These findings are in contrast to the recommendation of the Italian National Consensus Guideline 5 and a recent study from Italy showing that underdilation persisted and resulted in less HE. 21 Fortunately, an improved covered stent has been marketed recently (Viatorr CX) that allows stent adjustment to 8, 9, or 10 mm without spontaneous further selfexpansion. In any case, our results encourage dilation to 8 mm as a routine, independent of the degree of reduction of the pressure gradient, and to revise and dilate further if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…From the experience with H-graft calibrated shunts we know that 8 mm shunts were significantly better than large shunts (12 mm and above). 6,21 For TIPS, it has recently been reported that under-dilated covered TIPS (dilated to up to 6-7 mm in diameter) may cause less encephalopathy than "standard" diameter TIPS (8-10 mm in diameter), 22 but this is based on a single non-randomised retrospective study with a rate of overt hepatic encephalopathy of 54% at 1-year with standard TIPS (in the upper reported range) and of 26.9% with under-dilated TIPS. Moreover, the study reported no spontaneous dilation of the selfexpandable stents, which contrasts with the results of studies conducted over longer observation times.…”
Section: Current Challengesmentioning
confidence: 99%